The Effect of Corporate Social Responsibility on Bank Performance in South Africa - Naurikay, Bennett; Obalade, Adefemi (The Journal of Accounting and Management, 2023)
Objective: This study investigates the relationship between the corporate social responsibility (CSR) and financial performance (FP) of the leading commercial banks in South Africa. The study used annual time series data covering the period from 2002-2021. Prior Work: This study builds on the extant literature by examining the effect of CSR on different measures of financial performance (return on assets (ROA), Net profit after tax (NPAT) and net profit margin (NPM)) in order to provide robust evidence. Approach: A correlation analysis was used to examine the direction of the relationship between CSR and FP. The study further employed regression analysis to examine the effects of CSR on FP. Results: The overall finding is that CSR had a positive effect on ROA, NPAT and NPM for both Standard bank and Nedbank. This finding is in line with most of the studies conducted on the relationship between CSR and FP. Implications: This suggests that CSR is helpful in improving the performance of banks. The study recommends that the regulatory authority in South Africa should implement policies that encourage investment in corporate social responsibility. In addition, bank management must consider CSR investments as worthwhile for banks. Value: This study provides robust support for the profit relevance of CSR investment in the South African banking sector.